Economic inequality, distributive unfairness, and regime support in East Asia. Issue 2 (17th February 2023) - Huang, Xian; Zuo, Cai
ABSTRACT: The relationship between economic inequality and political support is not well established in previous empirical studies in part because people commonly misperceive the level of economic inequality. Moreover, people perceiving high economic inequality may not oppose the incumbent government or political regime because they consider the inequality fair. To better capture the political outcomes of economic inequality, we investigate the effects of perceived distributive unfairness on regime support. Using data collected from the fourth wave of Asian Barometer Survey (2014–2016), we find that perceived unfairness decreases support for the current political regime. We further examine three mechanisms through which distributive unfairness dampens regime support: changes of political value orientation, redistribution demand, and social trust. We find that political value orientation plays a greater mediating role than redistribution demand and social trust, meaning that distributive unfairness depresses regime support largely through its erosive impact on citizens' affective identification with authoritarian values that underpin regime support in East Asian societies. Moreover, we find that distributive unfairness is more detrimental to regime support in autocracies and lower-income groups. Our study corroborates the importance of distributive fairness for regime legitimacy and highlights the vulnerability of autocracies to distributive unfairness.